Unsur “Penasaran: Menarik dan Menggelitik” dalam “Permainan Bahasa” pada Teks Promosi Pariwisata - Ary Setyadi (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2022)
AbstractThe main and especially function of language, including Indonesian, is a communication tool, both in the form of spoken and written variety. The content of the message can be packaged in a straightforward manner/denotation or figure of speech/connotation. The existence of Indonesian as a tourism promotion tool, because tourism objects are not always packaged in a straightforward manner, but can be packaged in a figurative way (so that the form of "language games" is used). Because the existence of promotional texts that contain elements of the form of "language games" has strategic value, which is able to arouse a sense of "curious: interesting and tickling" (for potential tourists). Based on the results of data analysis, it was found that there are three kinds of promotional text forms that contain elements of the form of "language games", namely: 1. form of deviation (sentence structure pattern), 2. form of: a. ambiguous type, and b. game sounds of words (word elements), and 3. accuracy of diction. Research implementations departs from three strategic stages, as applicable in linguistic research, namely: 1. stage of providing/collecting data, 2. stage of data classification and analysis, and 3. stage of writing/compiling reports. The application of the theory departs from linguistic theory: phonology, morphology, syntax, and semantics. Application of these four fields implies the existence of: language, users, uses, and usage. Provision of data departs from the findings of the listener, and author's creation efforts. The existence of data and data analysis serves as an effort to prove, namely that the existence of promotional texts that contain elements of the form of "language games" has strategic value. Keywords: Strategic, language game, text, tourism promotion AbstrakFungsi utama dan terutama bahasa, termasuk bahasa Indonesia, adalah alat komunikasi, baik ragam lisan maupun tulis. Isi pesan dapat dikemas secara lugas atau majas. Keberadaan bahasa Indonesia sebagai alat promosi pariwisata, sebab objek pariwisata tidak selamanya dikemas lugas, tetapi dapat dikemas secara majas (sehingga memanfaatkan bentuk “permainan bahasa”). Teks promosi yang berunsur bentuk “permainan bahasa” bernilai strategis mampu membangkitkan rasa “penasaran: menarik dan menggelitik” (bagi calon wisatawan). Berdasarkan hasil analisis data didapatkan tiga macam bentuk teks promosi yang berunsur bentuk “permainan bahasa”, yaitu: 1. adanya bentuk deviasi (pola struktur kalimat), 2. adanya bentuk: a. tipe ambigu, dan b. permainan bunyi kata (unsur kata), dan 3. adanya ketepatan diksi. Pelaksanaan penelitian bertolak pada tiga tahapan strategis, yaitu: 1. penyediaan data, 2. klasifikasi dan analisis data, dan 3. penyusunan laporan. Adapun penerapan teori bertolak pada teori linguistik: fonologi, morfologi, sintaksis, dan semantik. Penerapan keempat bidang tersebut mengisyaratkan keberadaan: bahasa, pengguna, penggunaan, dan kegunaan. Adapun penyediaan data bertolak dari temuan penyimakan, dan upaya penciptaan penulis. Analisis data berfungsi sebagai upaya pembuktian, yaitu bahwa keberadaan teks promosi yang berunsur bentuk “permainan bahasa” bernilai strategis.Kata kunci: Strategis, permainan bahasa, teks, promosi pariwisata